Advances in gene therapy for respiratory diseases 2 - Engelhardt, John F. (Henry Stewart Talks, 2023)
Adeno-associated virus for airway gene delivery, Directed evolution of rAAV2 for airway transduction, rAAV2.5T transduces ferret airway epithelium, Human bocavirus 1 (HBoV1), rAAV2/HBoV1 transduces ferret airway, RNA viral vectors for gene therapy, Lentiviral-mediated phenotypic correction of cystic fibrosis pigs, Non-viral vectors for gene therapy of CF lung disease, LNP mRNA delivery to ferret airways, Mucolytics will be needed in severe disease states